Cardiac stress biomarkers after red blood cell transfusion in patients at risk for transfusion‐associated circulatory overload: a prospective observational study. Issue 9 (11th September 2018) - Callum, Jeannie L.; Cohen, Robert; Cressman, Alex M.; Strauss, Rachel; Armali, Chantal; Lin, Yulia; Pendergrast, Jacob; Lieberman, Lani; Scales, Damon C.; Skeate, Robert; Ross, Heather; Cserti‐Gazdewich, Christine
Abstract : BACKGROUND: Transfusion‐associated circulatory overload (TACO) is a leading cause of serious reactions. In regard to TACO, little is known regarding biomarkers as a predictor, their most informative timing, or thresholds of significance or differentiation from other reactions. STUDY DESIGN AND METHODS: In this study of inpatients at risk for TACO (age ≥ 50 years) receiving 1 red blood cell unit, cardiac biomarkers, brain natriuretic peptide (BNP), N‐terminal pro‐BNP (NT‐proBNP), and high‐sensitivity troponin were measured at baseline, 6 to 12 hours (except troponin) posttransfusion, and 18 to 24 hours posttransfusion. Primary outcome was a critical increase in biomarkers (>1.5‐fold increase and supranormal) at 18 to 24 hours. RESULTS: Fifty‐one patients were analyzed; 29% had cardiovascular disease, 73% had one or more cardiac risk factors, and 50% took cardiac or antihypertensive therapies. Although eight (16%) developed an increase in systolic pressure of at least 30 mmHg and four (8%) reported dyspnea and/or cough, none had TACO. At baseline, BNP level was more than 100 ng/L in 59% and NT‐proBNP was more than 300 pg/mL in 83%. A total of 25% had a BNP critical increase, 33% had a NT‐proBNP critical increase, and 2% had a troponin critical increase at 18 to 24 hours. Overall, 38% had at least one biomarker critical increase and NT‐proBNP/BNP concordance was 84%. An increase in the NT‐proBNP (>1.5‐fold increase and >300 pg/mL) at 18 to 24 hours was the commonest biomarker change. CONCLUSIONS: An increase of the NT‐proBNP at 18 to 24 hours may be the preferred surrogate marker for identifying a patient experiencing physiologic difficulty in handling the volume challenge. Larger studies are needed to clarify the risk of TACO for a given pretransfusion biomarker profile and the correlation between TACO and increase in biomarkers after transfusion.